Low temperature synthesis of metastable tetragonal yttria doped hafnia T-(Y-HfO2) nanoparticles through mechanochemical processing and annealing. Issue 10 (15th May 2021) - Qiu, Zanlin; Li, Cheng-Han; Jinschek, Joerg R.; Gouma, Pelagia-Irene
Abstract: For polymorphic binary metal oxides, such as HfO2, the availability of metastable phases with distinct physical and chemical properties opens a wide field of new applications. Hafnia (HfO2 ) is used as a thermal barrier coating in high temperature structural materials and as an electronic material (gate oxide) in the metal-oxide semiconductor field-effect transistors (MOSFETs). Its diverse functionality may be further tailored by phase selection and stabilization. The tetragonal polymorph with its high dielectric constant and wide bandgap is important in MOSFET applications. However, the temperature required to stabilize the metastable tetragonal phase is around 1700-1800 °C, making it difficult to synthesize large tetragonal nanoparticles or even bulk materials. In this project, tetragonal HfO2 (T-HfO2 ) nanoparticles were produced at relative low temperature (1100 °C) by employing mechanochemical processing with the addition of yttrium. Structural characterization using XRD, and HRTEM analysis revealed that the as-milled powders are a mixture of T-HfO2, residual monoclinic HfO2 (M − HfO2 ) and an amorphous component. Subsequent annealing transforms residual M − HfO2 and any remaining amorphous material into T-HfO2 as well. A viable route for stabilizing thermodynamically unfavored phases in the HfO2 system is described.